The consequences of the COVID-19 pandemic on mental health: A literature review - Diniz, Lara Zambon; Diniz, Luciana Zambon; Pascoal, Isabella Augusto; Pereira, Fernando Brockestayer Cortez; Diniz, Joana Degasperi; Dinz, Luiza Degasperi; Menezes, Ellen Diniz de; Machado, João Guilherme de Oliveira (Seven Editora, 2024)
The pandemic caused by the Coronavirus Disease (COVID-19) has modified, in countless ways, the psychosocial behavior of the population. Quarantine, updates provided by social media, and the rising number of deaths were some of the contributing factors. This is a descriptive study that seeks to analyze the consequences of the COVID-19 pandemic on the mental health of the population. Among the main groups impacted, health professionals on the front line of care, patients hospitalized in Intensive Care Units, patients with previously diagnosed psychiatric conditions, and those who have lost someone in their social life stand out. Medical and psychological follow-up of the population is essential, aiming at their mental well-being. DOI:https://doi.org/10.56238/sevened2024.001-050